Ultrasound evaluation of the renal pelvis in cats with ureteral obstruction treated with a subcutaneous ureteral bypass: a retrospective study of 27 cases (2010–2015). Issue 10 (October 2018) - Fages, Julien; Dunn, Marilyn; Specchi, Swan; Pey, Pascaline
Objectives: The objective of the study was to measure the preoperative and postoperative renal pelvic size and describe the ultrasound findings following successful decompression of a ureteral obstruction using the subcutaneous ureteral bypass (SUB) device in cats. Methods: This retrospective study assessed the measurement of the renal pelvis of 27 cats with unilateral (n = 21) or bilateral (n = 6) ureteral obstruction before (pre-t0 ) and after placement of a SUB during short- (before t0 + 3 months ) and long-term (after t0 + 3 months ) follow-up. Several qualitative ultrasound parameters were recorded for each cat. At both intervals, the last ultrasound examination was used for qualitative criteria and the mean pelvic size was recorded. The complications observed during follow-up were divided into obstructive and non-obstructive. Results: No qualitative ultrasound parameter was statistically significant. The presence of retroperitoneal or peritoneal effusion was rarely seen (n = 4/25 during the short term and n = 1/14 during the long term). Hyperechogenicity of the perirenal adipose tissue decreased in the long term. A statistically significant decrease in the width of the renal pelvis was noted in the short- (2.4 mm, range 0–7.0 mm) and long-term (1.7 mm, range 0–3.5 mm) follow-ups compared with the preoperative value (11.7 mm, range 0.9–41 mm). Three months following SUB placement, each cat without an obstructive complication had a pelvic width ⩽3.5 mm. Conclusions and relevance: Renal pelvic distension is at least partially reversible when ureteral obstruction is treated by placement of a SUB. Ultrasound monitoring is a useful tool to detect obstructive complications.